PENGOLAHAN DURIAN (Durio zibethinus) FERMENTASI (TEMPOYAK) - Neti Yuliana (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2007)
Tempoyak is fermented durian that is popular as a side dish and condiment prepared by placing durian pulp in jars to which salt is added, carefully mixed and tightly closed and kept for seven to ten days to let fermentation take place. Based on salt content, tempoyak can be categorized as tempoyak with low salt content (less than 5%) that result in sour tempoyak and tempoyak that has high salt content more than 5% (salty tempoyak). Law salt content is more favor for lactic acid bacteria (LAB) growth so the final acidity of tempoyak is higher than those with hight salt content. Durian fermentation process can be carried out trhough spontaneous fermentation or in under controlled fermentation with LAB starter addition, wet or dry starter. This last mean will shorthen the fermentation length to be 2-4 days with better microbiology quality. Tempoyak inoculated with wet starter has caharecterisitc watery concistency. Mean while, dry Pediococcus acidilactici application give tempoyak with more prefered sensory, less watery consistency and less acid taste as well as easier fermentation control. However, its adaptation time is longer than that in wet starter application. To enhance the sensory, some cane sugar can be added before tempoyak being fermented and the level of sugar added should consider the balance of the sour taste and sweet sensory of the final tempoyak. Keywords : pengolahan tempoyak, kultur cair, kultur kering, tempoyak asam dan tempoyak asin.